Bezobrazkowe badanie poziomu rozwoju kompetencji narracyjnej u dzieci jedno- i dwujęzycznych - Nott-Bower, Aneta (Postscriptum Polonistyczne, 2020)
The article author presents the method of evaluating monolingual and bilingual children’s narrative competence in Polish without the use of pictures. A test created for the purpose of the research evaluates a child’s ability to recreate a story previously heard without using any visual materials. The author presents the advantages of such test and its usefulness in different disciplines, including pedagogy, psychology and speech therapy. In bilingual children’s education it can help one assess the level of Polish language knowledge.